Meaning work: reworking institutional meanings for environmental governance. Issue 1 (2nd January 2019) - Riedy, Chris; Kent, Jennifer; Thompson, Nivek
Abstract : Effective environmental governance requires institutional change. While some actors work to change institutions, others resist change by defending and maintaining institutions. Much of this institutional work is 'meaning work', which we define as the practice of crafting, adapting, connecting and performing meanings to purposively create, maintain or disrupt institutions. This paper constructs a concept of meaning work that highlights agency in carrying meanings across scales and between discursive layers, while noting the structuring role of prevailing discourses. It grounds the concept using two environmental governance cases at very different scales: a local democratic innovation employed by Noosa Council in Queensland, Australia; and the international campaign to divest from fossil fuels. The cases demonstrate the diversity of meaning work and the difficulty of achieving deep discursive change. They point to the need for environmental governance practitioners to rework existing meanings to construct compelling stories for change, taking advantage of narrative openings.